Machining with the WalkingHex: A walking parallel kinematic machine tool for in situ operations. Issue 1 (2017) - Olarra, A.; Axinte, D.; Uriarte, L.; Bueno, R.
Abstract: In situ repair/maintenance of industrial installations is challenging working scenario considering the variety of operations that are required to be performed against the clock. The paper reports on a unique walking hexapod (WalkingHex) machine tool which has a set of key abilities: (i) walks autonomously to the place of intervention; (ii) calibrates autonomously and references itself against features on the ground; (iii) performs machining operations. The essential design and theoretical aspects are presented to allow the understanding of main working principles of the WalkingHex while a selected set of experimental trails show its ability to generate accurate features.